Nickel(ii) di-aqua complex containing a water cluster: synthesis, X-ray structure and catecholase activity. (20th January 2021) - Shit, Madhusudan; Maity, Suvendu; Bera, Sachinath; Mudi, Prafullya Kumar; Biswas, Bhaskar; Weyhermüller, Thomas; Ghosh, Prasanta
Abstract : A trans -diaquanickel(ii ) complex with a tetradentate aryloxyacetic acid ligand that forms a six membered water cluster in crystals and exhibits catecholase activity with a good turnover number is reported. Abstract : A trans -diaquanickel(ii ) complex of the type [(L 2− )Ni II (H2 O)2 ]· n H2 O (1 · n H2 O) was isolated, where LH2 is ( E )-2-(2-((2-hydroxyphenylimino)methyl)phenoxy)acetic acid (LH2 ), a tetradentate ligand. The molecular geometry of 1 · n H2 O was confirmed by single crystal X-ray structure determination. It is observed that in the crystal, coordinated water, bulk water and ligand oxygen atoms form six membered water clusters by OH⋯H interactions. 1 · n H2 O has emerged as a catalyst for the oxidation of 3, 5-di- tert -butylcatecholto 3, 5-di- tert -butyl- o -benzoquinone with a turnover number ( k cat ) of 4.46 × 10 2 h −1 in CH3 OH. During oxidation, the coordination of catechol to the nickel(ii ) centre and the formation of an o -benzosemiquinone intermediate were confirmed by a nickel based EPR signal, ESI mass spectrometry and UV-vis spectra. 1 · n H2 O exhibits an irreversible anodic peak at 0.83 V versus the Fc + /Fc couple due to the phenoxyl/phenolato redox couple, authenticated by DFT calculations.